Reduction of Collagen Powder Size from Snakehead Fish Skin (Channa Striata) Using Desolvation Method - Rini Agustin; Indri Istiqomah; Rahmi Nofita R (Postgraduate, University of Mataram, 2024)
The size of collagen which was isolated from the skin of snakehead fish (Channa striata) is important in relation to the pharmaceutical applications of collagen, especially in collagen solubility and its dispersion systems for topical applications. In smaller sizes, even reaching nanometer sizes, it is hoped that it will improve the penetration of collagen through the skin when applied. The aims of this study is to obtain collagen microparticulates isolated from the skin of snakehead fish (Channa striata) in a smaller size using the desolvation method with variations in the ratio of collagen and ethanol (w/v) 1:1 and 1:2, stirring time 15, 30, 60 , 120 minutes, and the stirring speed of 3000, 6000, 12000 rpm. The collagen was characterized by its physicochemical properties including particle size, thermal properties, X-ray diffraction patterns, morphology with SEM and infrared spectra. The results of characterization of collagen after treatment with the ratio of the addition of collagen and ethanol 1:2, for 1 hour, and a stirring speed of 12000 rpm showed the smallest particle size was 24.746 μm. Morphological analysis showed random coils indicating the nature of collagen fibrils and no change in functional group analysis. Thermal analysis showed a decrease in the melting point peak from the thermogram results, as well as the intensity of the X-ray diffraction pattern which still shows the characteristics of collagen. The results showed that there was a reduction in the size of the new collagen particles down to the micrometer scale and there was no change in the structure of the collagen triple helix.